Identification polymorphism of LHR and FSHR genes in Indonesian Holstein dairy cattle associated with productive and reproductive traits - YULIATI WAHYU SETYORINI; EDY KURNIANTO; SUTOPO SUTOPO; SUTIYONO SUTIYONO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Setyorini YW, Kurnianto E, Sutopo, Sutiyono. 2023. Identification polymorphism of LHR and FSHR genes in Indonesian Holstein dairy cattle associated with productive and reproductive traits. Biodiversitas 24: 2898-2905. Luteinizing and follicle-stimulating hormones and their receptors play an important role in the reproductive system’s hormonal activity and physiological function. This study aimed to identify the genotype variation of the Luteinizing Hormone Receptor (LHR) gene exon 11 and the Follicle-stimulating Hormone Receptor (FSHR) gene exon 10 and to elucidate the associating between polymorphism with the milk and reproductive traits in dairy cattle. A total of 100 samples of deoxyribonucleic acid (DNA) from Indonesian Holstein dairy cattle were used in this study. Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) was performed for genotyping of the Single Nucleotide Polymorphism (SNP) of the LHR and FSHR genes with the HhaI and AluI restriction enzymes, respectively. The collected phenotype data were milk production, quality, and reproductive trait. In addition, the general linear model procedure in the SAS program was carried out to investigate the association of genotypes with productive and reproductive traits. The results showed that the LHR gene in the population of this study was monomorphic, while the FSHR gene was polymorphic with three genotypes, namely CC, CG, and GG. The sequences of the FSHR gene indicated the presence of a mutation at nucleotide number 2037 that substitutes cytosine for guanine. Cows with the CC genotype showed better parameter service per conception (P<0.05) than the other genotypes but did not correlate with other reproductive parameters and milk traits. Therefore, it was concluded that SNP g.2037C>G polymorphism at FSHR gene exon 10 was identified in the Indonesian Holstein Dairy cattle population and associated with service per conception parameters but not with milk trait.